(untitled) (Journal of Economic Research & Business Administration, 2018)
In the conditions of formation of innovative economy, the main factor of development of subjects of the economy is the intellectual potential. The change in the role of knowledge in social and economic development requires a fundamental change in the function of the social institution of education in the material and spiritual reproduction of the living conditions of society and man. The combination of the capabilities of individual subjects and scientific and pedagogical teams in the implementation of educational, scientific and innovative activities determines the intellectual potential of higher education institutions, and contributes to the development and formation of an effective investment policy at individual enterprises, organizations and institutions. One of the main tasks of regional development and the country as a whole is the creation and development of such an organizational and functional model of the university that would allow managing the adaptation of education and science in the emerging competitive environment. It is in such an environment, under the influence of internal and external factors, the intellectual potential of a modern university, in the unity of its cultural, educational, scientific and innovative components The mechanism for managing the intellectual potential of universities should be based on the interaction of external and internal factors of their current activities that affect the competitiveness of educational institutions of higher professional education in the market of educational services.